The association between cerebrospinal ferritin and soluble triggering receptor expressed on myeloid cells 2 along Alzheimer's continuum - Shi, Xiaolei; Zhong, Xiaomei; Zhou, Huarong; Zhou, Nan; Hu, Yachun; Ning, Yuping; , Alzheimer's Disease Neuroimaging Initiative (Frontiers in Neurology, 2022)
Brain iron accumulation, which is indicated in the cerebrospinal fluid (CSF) ferritin, is associated with the development of Alzheimer's Disease (AD). Studies have indicated that iron deposition might participate in Alzheimer's pathology through the induction of microglial activation. A soluble triggering receptor expressed on myeloid cells 2 (sTrem2) in CSF is increasingly recognized as a reliable indicator for microglia activity in the brain and participates in the development of neuroinflammation. However, the association between CSF ferritin and sTrem2 under the AD continuum has not been well-established. We enrolled individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database. Participants were classified into healthy controls (HC, n = 46) and AD continuum (n = 105) in the combined strata of Amyloid/Tau/Neurodegeneration (ATN) mode and Clinical Dementia Rating (CDR) criteria. The associations between CSF ferritin (indicating iron burden) and sTrem2, as well as AD pathology, which is reflected by Aβ42, t-tau, and p-tau in CSF, were explored. CSF ferritin was significantly associated with sTrem2 among all participants (β = 0.517, P < 0.001, FDR < 0.001), HC (β = 0.749, P = 0.006, FDR = 0.010), and AD continuum (β = 0.488, P < 0.001, FDR < 0.001), respectively. However, ferritin predicted the accelerated sTrem2 level in those with high ferritin (β = 0.549, P = 0.036, FDR = 0.045). In conclusion, CSF ferritin serves as a potential biomarker of Trem2-indicated microglia function.